Rate of success for a groundwater drilling program planned from AEM, Gascoyne River, WA. Issue 1 (1st December 2018) - Davis, Aaron; Munday, Tim; George, Richard
Abstract : In a collaboration between Department of Agriculture and Food, Western Australia (DAFWA) and CSIRO, funded by the Western Australia Government's Royalties for Regions Program and the Gascoyne Foodbowl Project, the Gascoyne River AEM Aquifer and Groundwater Characterization Project was established with the aim of determining whether airborne electromagnetic (AEM) data can be employed to better map attributes of the unconfined alluvial aquifer beneath and adjacent to the ephemeral Gascoyne River. One major aspect of the project was to produce drilling targets, based on interpretation of AEM data, for groundwater production. In this presentation, we briefly recapitulate our method and discuss the result of the drilling campaign that ensued. We show that our exploration targets have resulted in overwhelming success in the conversion of exploration wells to production bores; and that the production wells produce greater yields of better quality groundwater than previous campaigns that were conducted through step-out drilling. We show that interpretation of the AEM inversions allowed us to map the aquitard layers that define the bottom of the Gascoyne River Old Alluvium aquifer system, determine the extent of the saltwater intrusion from the nearby Indian Ocean, and to calculate the overall volume of the aquifer system. These calculations allow us to provide estimates of total groundwater volume contained in the aquifer for sustainable production.